Contribution to the knowledge of the scattered villages in the small and medium size mountains of northern Romania (Țibău Mountains case study) - Cezar CERNUȘCĂ (Georeview, 2021)
The present study is about the smallest rural settlements in the upper Bistrița river valley geographical region and even in the larger ethnographic region of Țara Dornelor. The main effort was made to analyze these mountain hamlets using available sources such as direct and indirect observation and gathering of credible information from the locals by verifying and synthesizing it. In doing so, we were able to establish that the inhabitants of these mountain hamlets have overcome the harsher climatic conditions in the small and medium mountains of northern Romania, managing to adapt and even prosper until recently due to their resilience, the abundance of valuable resources and other day-to-day living advantages.